Portuguese football - Pestana Barros, C. (Journal of Sports Economics, 2006)
In this article, the author characterizes the financial crisis in Portuguese football on the basis of data published by Deloitte and Touche in its annual reports on the financial ramifications of the sport in Portugal. A strategy to be applied to the case, with a view to improving the clubs' financial management, is presented.